The interplay between nonsense-mediated mRNA decay (NMD) and the unfolded protein response (UPR) in response to myocardial infarction - Fernandes, Rafael (2017)
Nonsense-mediated mRNA decay (NMD) is a surveillance pathway that recognizes and degrades mRNAs carrying premature translation-termination codons (PTCs), protecting the cell from potentially harmful truncated proteins. Furthermore, recent studies have demonstrated that NMD is also a mechanism of gene expression regulation. This feature is reflected on its ability to regulate the cell response to many stress conditions, such as endoplasmic reticulum (ER) stress, hypoxia, reactive oxygen species, and nutrient deprivation. Stress conditions, specifically ER stress, has been related to myocardial infarction, a pathological state that occurs during ischemia, where nutrient and oxygen deprivation in the heart causes aggregation of proteins in the ER and the activation of the the three arms (ATF6, IRE1α and PERK) of the unfolded protein response (UPR) to mitigate the stress and avoid cell death. Given that NMD was seen to be able to regulate the UPR and to protect cells from death during ER stress, in this work we intend to study the impact of NMD in the PERK-mediated response to ER stress induced by ischemia during myocardial infarction, and its impact to the pathophysiology of this disease. For this purpose, differentiated H9c2 cells will be used as a model of cardiomyocytes, which will help us to dissect the crosstalk between NMD and UPR in myocardial infarction-mimicking conditions. By now, we have already established the differentiation protocol for the H9c2 cell line in order to obtain mature cardiac-like cells, and we are now optimizing and establishing the experimental conditions to further develop this project.